BRCA 1/BRCA 2 Pathogenic/Likely pathogenic variant patients with breast, ovarian, and other cancers - KÖSTEK, OSMAN (My University, 2022)
The demographic and clinical characteristics of patients who have BRCA 1/BRCA 2 pathogenic/likely pathogenic variants may differ from their relatives who had BRCA-related cancer. In this study, we aimed to demonstrate the clinical and demographic findings of patients who had BRCA-related cancer and to assess the differences comparing their relatives who had BRCA-related cancer with breast, genital tract, prostate, and pancreas cancers as well. The results of sequencing analysis of 200 cancer patients (190 women, 10 men) who have been directed to genetic counseling with an indication of BRCA1/BRCA2 testing from different regions across 9 medical oncology centers were retrospectively analyzed. A total of 200 consecutive cancer patients who harbored the BRCA1/BRCA2 pathogenic/likely pathogenic variant (130 (65%) patients harbored BRCA 1 pathogenic/likely pathogenic variant, and 70 harbored BRCA 2 pathogenic/likely pathogenic variant) were included. Of these, 64.0% had breast cancer (43.8% of them had the triple-negative disease, and about 2.3% had only the HER-2 mutant), 31.5% had genital cancers (92.1% of them had ovarian cancer, 3.2% had endometrium, and 1.6% had peritoneum cancer as the primary site and mostly serous adenocarcinoma was the most common histopathology and 14.3% of the patients had endometrioid adenocarcinoma), 3.5% had prostate (median time from metastasis to castration-resistant status was 28 months) and 1.0% had pancreas cancer. Newly diagnosed cancer (breast and ovary) patients who had BRCA 1/BRCA 2 pathogenic/ likely pathogenic variant were younger than their previous cancer diagnosed (breast, ovary, and pancreas) parents who harbored BRCA pathogenic/likely pathogenic variant. We suggest that the genetic screening of BRCA 1/ BRCA 2 pathogenic/likely pathogenic variant is needed as a routine screening for those with a personal or family history of breast, ovarian, tubal, or peritoneal cancer. In addition, once BRCA 1 or BRCA 2 germline pathogenic variant has been identified in a family, testing of at-risk next-generation relatives earlier can identify those family members who also have the familial pathogenic variant, and thus need increased surveillance.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); GENETİK VE KALITIM; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; GENETICS & HEREDITY; Genetik; Genetik (klinik); Genetics; Genetics (clinical); BRCA 1; BRCA 2; breast; genital cancers; pancreas; prostate; BRCA 1; BRCA 2; breast; pancreas; genital cancers; prostate; pancreas